"I Didn't Know It Existed Before You Called": Protestant Clergy Experience, Education and Perceptions Regarding Genetics. Issue 2 (10th October 2012) - Lemons, Jennifer; Ragsdale, Judy; Vaughn, Lisa; Grossoehme, Daniel
Abstract: Despite the intrinsic role religious/spiritual (hereafter, R/S) beliefs have in patient clinical decision‐making and crisis coping, there is little research exploring the relationship that exists between clergy (professionals who provide R/S counsel and guidance) and genetic counseling patients. This qualitative, exploratory study was designed to explore Protestant clergy ( N  = 8) perceptions of and experience with genetics‐related issues. Data analysis revealed that a wide range of R/S perceptions regarding genetics‐related issues exist within Protestantism, Protestant clergy have a basic understanding of genetic testing and conditions, and while directive counseling is inherent to Protestant clergy counseling, there appears to exist two opposing styles: unbiased and biased. Based on this information, there are two main implications for genetic counseling clinical practice. First, R/S assessments need to be increasingly implemented into genetic counseling sessions, so that the psychosocial needs of patients with specific R/S beliefs can be identified and addressed. An increase in R/S assessments may be accomplished by increased exposure in genetic counselor training, continuing education opportunities, and by establishing relationships with board‐certified, professional chaplains. Second, genetic counselors can influence the genetic education and experience of clergy by raising awareness within their own R/S assemblies. Doing so can also serve to further educate genetic counselors in the R/S beliefs of their own traditions, thus increasing sensitivity, empathy and the quality of care provided.